2014
DOI: 10.1111/1750-3841.12387
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Chitinase‐Producing Bacillus and Paenibacillus Strains from Salted and Fermented Shrimp, Acetes japonicus

Abstract: Chitinases catalyze the conversion of chitin and are produced by a wide range of bacteria. The biological applications of these enzymes have been exploited in food and pharmaceutical industries. We isolated 2 halophilic chitinase-producing novel strains of bacteria-SCH-1 and SCH-2 from Saeu-jeot, a traditional Korean salted and fermented food made with shrimp (Acetes japonicus). The isolated strains- SCH-1 and SCH-2 were Gram-positive, rod-shaped, endospore-forming facultative anaerobes, with strain SCH-2 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…obtained from salted and fermented shrimp (Han et al . ). It appears that the fatty acid composition of Bacillus sp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…obtained from salted and fermented shrimp (Han et al . ). It appears that the fatty acid composition of Bacillus sp.…”
Section: Discussionmentioning
confidence: 97%
“…from salted and fermented shrimp that showed the highest level of chitinase activity at a pH just beyond 7.0 and when cell growth was in a stationary phase (Han et al . ). Other researchers have suggested that B. laterosporus (Shanmugaiah et al .…”
Section: Discussionmentioning
confidence: 97%
“…After culturing and appropriate incubation time, chitinolytic activity is visualized by a clear zones of chitin hydrolysis around colonies, as shown in Fig. 13.1f (Han et al 2014 ). Two chitinolytic bacteria, HCh1 and HCh2 strains identifi ed as genera Saccharospirillum and Arhodomonas , respectively were ( 2009b ) isolated from hypersaline lakes in Russia.…”
Section: Chitinasesmentioning
confidence: 99%
“…strain SCH-1 and Paenibacillus sp. strain SCH-2 isolated from a salted and fermented food (Han et al 2014 ) and Haloanaerobacter chitinovorans isolated from a solar saltern (Liaw and Mah 1992 ) exhibited chitinolytic activity. A moderately halophilic bacterium, Virgibacillus marismortui strain M3-23 that isolated from a Tunisian shallow salt lake produced a chitinase in the absence or presence of salt.…”
Section: Chitinasesmentioning
confidence: 99%
“…We previously reported isolation of chitinolytic Bacillus and Paenibacillus sp. from SFS using biochemical, phenotypic, and 16S rRNA‐based molecular phylogenetics study (Han and others ). Another study documented the bacterial communities of traditional and fermented seafoods from Jeju island of Korea using 16S rRNA gene‐clone library analyses and culture isolation (Kim and Park ).…”
Section: Introductionmentioning
confidence: 99%